Sastra Lingkungan sebagai Praktik Pembelajaran Berkelanjutan: Studi Deskriptif pada Guru SMP - Aprilia Nur Azizah; Wahda Rahma Laila; Ari Ambarwati; Dyah Werdiningsih (Badan Pengembangan dan Pembinaan Bahasa, 2025)
Environmental literature has strategic potential in sustainable education because it is able to convey ecological values in an affective, critical, and contextual manner. This study aims to describe the practice of environmental literature learning by junior high school teachers in East Java as a form of sustainable learning implementation with consideration of gender dimensions. The novelty of this study lies in presenting the perspective of teachers as the main actors who build eco-literacy through symbolic-affective interpretations of nature, thereby reflecting emotional and reflective relationships with environmental issues, in contrast to previous studies that focused more on texts or student responses. This study uses a descriptive mixed-methods approach, through closed questionnaires (Likert scale) and open-ended questions, which are analyzed quantitatively and thematically using the Miles & Huberman model. The results show the dominance of teachers' positive attitudes towards environmental literature despite obstacles and gaps in knowledge and practice. In addition, there is a complementary gender polarity that shows the dominance of male teachers with concrete-active strategies, while female teachers excel in reflective-literary strategies. The conclusion of the study confirms that environmental literature functions as an effective ecological-pedagogical space for reflection, with gender polarity being synergistic as a transformative force. Implicitly, these findings can form the basis for the development of contextual and applicable environmental literature curation at the school level. Abstrak Penelitian ini bertujuan untuk mendeskripsikan praktik pembelajaran sastra lingkungan oleh guru SMP di Jawa Timur sebagai implementasi pembelajaran berkelanjutan dengan mempertimbangkan dimensi gender. Penelitian menggunakan metode mixed-methods deskriptif. Data dikumpulkan melalui kuesioner tertutup berbasis skala Likert dan pertanyaan terbuka yang diberikan kepada guru SMP. Data kuantitatif dianalisis secara statistik deskriptif, sedangkan data kualitatif dianalisis secara tematik menggunakan model analisis interaktif Miles dan Huberman yang meliputi reduksi data, penyajian data, dan penarikan simpulan. Hasil penelitian menunjukkan bahwa guru memiliki sikap positif terhadap pemanfaatan sastra lingkungan dalam pembelajaran, namun masih terdapat hambatan pada aspek penguasaan konsep dan implementasi pedagogis. Analisis berdasarkan gender memperlihatkan adanya polaritas komplementer, yakni guru laki-laki cenderung menerapkan strategi pembelajaran yang konkret dan aktif, sementara guru perempuan lebih dominan menggunakan pendekatan reflektif dan literer. Simpulan penelitian menegaskan bahwa sastra lingkungan berfungsi sebagai media refleksi ekologis-pedagogis yang efektif, dengan perbedaan strategi berbasis gender yang bersifat sinergis dan berpotensi memperkuat transformasi pembelajaran berkelanjutan. Temuan ini berimplikasi pada perlunya pengembangan kurasi sastra lingkungan yang kontekstual dan aplikatif untuk mendukung praktik pembelajaran di tingkat sekolah menengah pertama.